The storyteller : a novel - Picoult, Jodi, 1966- (Emily Bestler Books/Washington Square Press, 2013)
Sage Singer becomes friends with an old man who is particularly beloved in her community after they strike up a conversation at the bakery where she works. Josef Weber is everyone's favorite retired teacher and Little League coach. One day he asks Sage for a favor, to kill him. Shocked, Sage refuses, but then he tells her he deserves to die. Once he reveals his secret, Sage wonders if he is right. Can someone who has committed a truly heinous act ever redeem themselves with good behavior? Should you offer forgiveness to someone if you are not the party who was wronged? And most of all, if Sage even considers his request, is it murder, or justice? What do you do when evil lives next door?